INOVASI APLIKASI TEKNOLOGI TEPAT GUNA ALAT PENYIANG GULMA PADI UNTUK GAPOKTAN TUNAS SAKATO DESA TOBOH PALABAH PARIAMAN - Irzal Irzal; Nelvi Erizon (Jurnal Vokasi Mekanika (VoMek), 2020)
Pests on rice are a factor that affects the quality and quantity of yields. One of the pests that hinder the growth of rice flowers is weeds. This community service activity aims to overcome problems and assist farmers in the process of handling their rice. From the results of the initial review of the community service team in the village of Toboh Palabah, there were several problems or concerns faced by rice farmers. The problems faced by farmers in weeding activities. Weeds, which are pests in the form of wild plants among rice plants, are a threat to rice growth. Usually farmers overcome this problem by removing the weeds manually, there has never been a machine known to the farmers to solve the weed problem. This activity requires a lot of energy and a long time. This complaint is a problem that will be given a solution. Through this service activity the community service team offers innovations to make weed eliminators using machines. The science and technology offered in this activity is the use of a 55 cc engine as a driver and will be transmitted to a blade designed to eradicate rice weeds